PERSEPSI SISWA TENTANG MANIFESTASI TUGAS-TUGAS PERKEMBANGAN REMAJA SISWA KELAS XI SMA.NEGERI 11 SAMARINDA - MERLY HANDAYANI (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2020)
AbstractYouth development tasks are tasks that arise at or around a certain period of individual life, but in reality not all students are familiar with developing youth development tasks. The formulation of the problem in this study is "What are the students' perceptions about the manifestation of the youth development tasks of class XI in SMA. Negeri 11 Samarinda 2014/2015 Academic Year". While the purpose of this study was to study students' perceptions about the manifestation of the task of developing class XI youth in SMA Negeri Negeri 11 Samarinda in the Year of Learning. This type of research is descriptive qualitative where the focus of research is students' perceptions about the manifestation of youth development tasks. This research was carried out in high school. Negeri 11 Samarinda with research participation was a class XI student at SMA Negeri 11 Samarinda in the 2014/2015 academic year that encouraged 144 students to become writers taking a sample of 75% of the total population, namely 108 students. The data collection method used was a questionnaire as the main method and documentation as a complementary method. While the data analysis technique was the interval and percentage formula. From the results of data management in 108 class XI students of SMA Negeri 11 Samarinda, 108 respondents, then 47 students of respondents had a good perception, with a percentage of 43.51%, 19 students had a very good perception, with a percentage of 17.59%, 36 students have a pretty good perception, however there are still students who have a bad perception that can be seen from the data above about 6 students or 5.55%. The results of the study showed that students' perceptions about the manifestation of youth development tasks, GOOD, because seen from 108 students as many as 47 students with a percentage of 43.51% had a GOOD perception about the manifestation of youth development tasks in SMA Negeri XI Samarinda.Keywords: Perception, Manifestation, Youth Branching